Erótica e ontologia : um ensaio sobre a questão da ontoteologia no pensamento de Orígenes de Alexandria - Marques, Lúcio álvaro (2014)
Two questions have supported our research: why is there something rather than nothing? (G. Leibniz) and the love of God, to be understood, presupposes the human love? (J. Y. Lacoste). They punctuate fundamental elements to the divine understanding. Being and love, since the Greek, Semitic and Johannine heritage, raise a question about the convergence or divergence between the concepts. Aware of the platonic (which puts the good beyond being ) and Aristotle‟s (which states God as beyond the intellect ) understandings, and also aware of Lacoste and Ricoeur readings about the sense and reach of being and love in the Western tradition, we ask: is it possible to understand and is it necessary to establish a relation between being and love to the understanding of God? That‟s the question we face by criticizing the ontotheology: the diversion operated by the early Christian thought about the sense of being and it forgetfulness, according to Heidegger, the Lévinas‟ refusal of the neutrality of the ontological thought, the search of a speech that thinks God without the contamination of being, the attempt of destruction of the idolatry of being and the understanding of a God that loves without Being by Marion. We don‟t judge enough the proposals of the criticism to the being of the ontotheology (Heidegger), the refusal of being (Lévinas) and the exclusive support to love (Marion), so were turn to the early Christian thought (Origen of Alexandria) to verify if we find a formulation of the divine understanding which did not restrict itself to the object of the ontotheological criticism as well as the exclusive theological speech about love. A curious formulation of our question is found in Joseph S. O‟Leary when he names the endogenous oxymoron to the Western philosophy as the necessity of reconciliating individuality and universality, liberty and logical necessity, personal God and enough reason. To affront the question, we turn to the first system of the early Christian thought. Origen of Alexandria seemed to us to be a reliable witness of the effort to conjugate the Greek heritage of being to the semitic tradition of the Exodus Metaphysics, beyond the Christian understanding of love. However, this undertaking claimed the formulation of a divine, unique and trinity ontology, and a divine and human erotics. At last, we verify the possibility of an articulation between the erotics, by means the possibility of the Impassive (passio caritatis Impassibilis), and the ontology, unique in the essence and - trinit in the hypóstases (mía ousía trêis hypostáseis), because this way we would answer the fundamental question not only about the Metaphysics but also about the Theology: is it possible to understand God as being and love? The possibility of an answer to the question depends on the conjunction between being and love in a concrete unicity, that is, is it possible to understand the unicity and the universality of Logos identifying them to the personified Logos?